Autumn Daily Characteristics of Land Surface Heat and Water Exchange over the Loess Plateau Mesa in China - 文军 韦志刚 吕世华 陈世强 奥银焕 梁玲 (Advances in atmospheric sciences, 2007)
The Loess Plateau, located in northern China, has a significant impact on the climate and ecosystem evolvement over the East Asian continent. In this paper, the preliminary autumn daily characteristics of land surface energy and water exchange over the Chinese Loess Plateau mesa region are evaluated by using data collected during the Loess Plateau land-atmosphere interaction pilot experiment （LOPEX04）, which was conducted from 25 August to 12 September 2004 near Pingliang city, Gansu Province of China. The experiment was carried out in a region with a typical landscape of the Chinese Loess Plateau, known as ＂loess mesa＂. The experiment＇s field land utilizations were cornfield and fallow farmland, with the fallow field later used for rotating winter wheat. The autumn daily characteristics of heat and water exchange evidently differed between the mesa cornfield and fallow, and the imbalance term of the surface energy was large. This is discussed in terms of sampling errors in the flux observations-footprint; energy storage terms of soil and vegetation layers; contribution from air advections; and low and high frequency loss of turbulent fluxes and instruments bias. Comparison of energy components between the mesa cornfield and the lowland cornfield did not reveal any obvious difference. Inadequacies of the field observation equipment and experimental design emerged during the study, and some new research topics have emerged from this pilot experiment for future investigation.